Increasing MSME Productivity Towards a Green Economy and Sustainable Growth - Putera, Made Pranata Wibawa Ade; Maradona, Agus Fredy (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to identify obstacles and solutions to increase the productivity of micro, small, and medium-sized enterprises (MSMEs) and to explore factors that contribute to sustainable businesses in the transition to a green economy in the German Beach Area of Banjar Segara Kuta, Bali. A qualitative method was used for data collection. Data were collected through interviews with key, expert, and supporting informants. Data analysis techniques use triangulation. The results revealed that to increase productivity and business sustainability towards a green economy, related parties must consider internal factors such as environmental awareness and collaboration with stakeholders, as well as provide coaching and education to improve the ability of MSME actors. This includes education related to the green economy as a form of MSME business sustainability efforts in the German Beach Area of Bali's Kuta district.